The impact of oriental studies on the methods of writing the biography of the Prophet - Althubiti, Amal Obead (Journal of Islamic Sciences, 2021)
The study aimed at identify the most prominent similarities raised by orientalists against the Prophet’s biography, and to shed light on the most prominent Muslim scholars who responded to these suspicions. The study used the critical inductive approach, and the study reached many results, most notably: that intolerance and prejudice were dominating the writings of the ancient Orientalists due to their being affected by the spirit of religious fanaticism that was dominant and crystallized by the impact of the Crusades, and due to their weak knowledge of the Arabic language, and the lack of resources available to them. However, since the early modern times, the West has not been free of moderate thinkers who have praised Islam, but since the nineteenth century interest began to study and print Arabic manuscripts, and Orientalists began studying the history of the East for itself, following the scientific method that had made great progress in the West.